Engineering design considerations in the development of temporary shelters for disaster-stricken areas in the Philippines - Teodoro, Joseph Brigham N.
The current situation in the supply and construction of temporary shelters for disaster-stricken areas especially in the Philippines requires special attention and assessment. This study aims to further assess the problems and propose an efficient construction system of temporary she lters with engineering design considerations. This is done by analyzing twenty temporary shelter systems locally and abroad. The main components analyzed are the shelter's foundation system, framing system, wall, flooring and roofing materials. After the analysis, design criteria are made and compared if conforming to acceptable standards. These design criteria serve as the attributes to be weighed in the ranking of materials. The Multi-Attributed Approach (MAA) in ranking alternatives is the method used in selecting the best materials to be recommended for the construction of the temporary shelter system. Results show that a steel leg anchored to a concrete footing is the best type of foundation. Light gauge framing is also the most efficient framing system. Fluted polypropylene, aluminum panels and corrugated G.I. sheets are the best materials for wall, flooring and roofing, respectively. The architectural layout from another study is also adopted and consolidated to come up with a proposed shelter system. As a final output, the shelter configuration is presented.